Exploring the Effectiveness of Fleming’s Multi-Sensory Visual, Auditory Kinesthetic Technique to Teach Vocabulary at Primary Level - Rafiq, Hira; Aziz, Sabah; Shahzadi, Iram (Pakistan Languages and Humanities Review, 2024)
Vocabulary learning is very crucial to be fluent in any language, specifically for second language learning. In Pakistan, teachers often rely on traditional methods like cramming or rote learning to teach vocabulary to second language learners. As a result, students associate words and their meanings with specific texts, limiting their ability to apply these words in varied contexts. To cope with this problem, the researcher employed Fleming’s (2006) multimodal technique which is the Visual, Auditory, and Kinesthetic technique to teach vocabulary. The research is an experimental study. Pretests and posttests are administered to examine the impact of Visual, Auditory, and Kinesthetic techniques on vocabulary learning of SLLs (Second Language Learners). The sample is selected through stratified sampling. There are 60 students in one class. This group is taught by lesson plans based on the VAK model. The pretests and posttests are analyzed through Rcampus rubrics. After marking them through rubric the data is analyzed through an independent sample t-test. Significant results have been seen that are indicated by p value which is .000. The research is helpful for language teachers who teach vocabulary to second language learners along with students.